The The Chemical Characteristic of Manila Duck Sausage Processed by Using Purple Sweet Potato Flour as Subtitute of Tapioca - Yakob Robert Noach; Agatha Feriyanti Fore Kehik; Gertruida Margareth Sipahelut (Program Studi Peternakan, Fakultas Pertanian Universitas Timor, 2022)
Experiment aims to determine the substitution effect of tapioca by purple sweet potato flour on antioxidant, fat oxidation, fat content and pH of Manila duck sausage. Completely randomised design with 5 treatments and 3 replications was applied in this experiment. Those treatment were: P0 = 100% of tapioca; P1 = 25% purple sweet potato flour + 75% tapioca; P2 = 50% purple sweet potato flour + 50% tapioca; P3 = 75% purple sweet potato flour + 25% tapioca; dan P4 = 100% purple sweet potato flour. Variable measured were: antioxidant, fat oxidation, fat content and pH. The result showed that treatments have close significant (P<0.01) on antioxidant and fat oxidation, significant (P<0.05) on pH and no significant (P>0.05) on fat content. It can be concluded that insreasing of purple sweet potato flour substitution up to 100%, producing the best chemicals characteristic of Manila duck sausage which indicated by increase of antioxidant, decreasing of fat oxidation, lower fat content and pH of sausage.